Corpus Linguistics for School Language Planning and Curriculum Development: A Comparative Study of Modern Arabic Literary and School Text Corpora/ لسانيات المدونات مدخلًا للتخطيط اللغوي المدرسي وتطوير المناهج الدراسية: دراسة مقارنة بين مدونة النصوص الأدبية العربية الحديثة ومدونة النصوص المدرسية - Hafid Maachi; Hakima Khamar; Lutfi Omar Abubkr (Ijaz Arabi Journal of Arabic Learning, 2026)
Students in many Arab countries experience a noticeable decline in their linguistic repertoire, accompanied by a reduction in the lexical diversity of contemporary school textbooks. This situation has resulted in a clear linguistic gap between the expressive, semantically rich classical Arabic used in literary texts and the simplified, functional language that characterizes modern educational materials. In response, the present study highlights the need to adopt corpus linguistics as an objective, data-driven methodology to support language planning and curriculum development, thereby ensuring a balanced integration of literary depth and pedagogical clarity. The study adopted a corpus-based approach by constructing two linguistic corpora. The first contained Modern Arabic Literary written by major authors between 1940 and 1970, while the second consisted of texts drawn from current school textbooks. Both corpora were analyzed using Sketch Engine, with a focus on quantitative and qualitative differences in lexical richness, syntactic patterns, and rhetorical features. The findings revealed that the modern Arabic literary corpus displays a high level of linguistic, semantic, and stylistic richness that can reinforce students’ linguistic awareness and aesthetic appreciation. Conversely, the school textbook corpus is dominated by simplified constructions and utilitarian vocabulary, and the contrast between both corpora reveals a significant lexical gap that may negatively affect the development of linguistic and cognitive competencies among students. The study concludes that corpus linguistics provides a reliable analytical framework for assessing and improving curricular balance and recommends reintegrating culturally and rhetorically valuable vocabulary into educational materials, grounded in empirical linguistic evidence.